TINDAK TUTUR EKPRESIF DALAM FILM “QODRAT” KARYA GEA REXY, ASAF ANTARIKSA DAN CHARLES GOZALI (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the types of expressive speech acts used by the characters in the film Qodrat (2022) and their function in character development and the storyline. This film was chosen because, in addition to its horror genre, it also contains strong Islamic and spiritual values, making it an interesting object for pragmatic studies. This research uses a qualitative approach with a descriptive method and a case study design. Primary data were obtained from the dialogues of the characters in Qodrat, while secondary data were obtained from supporting literature. Data collection techniques were carried out using listening and note-taking techniques. The analysis was conducted based on the speech act theory proposed by John Searle and Wijana's opinion on expressive speech acts. The results show that in Qodrat, various types of expressive speech acts are present, such as expressions of congratulations, thanks, apologies, praise, blame, and condolences. The function of these expressive speech acts not only describes the characters' emotional states but also strengthens the narrative meaning and creates a horror and religious atmosphere in the film.